A conjugated microporous polymer material and its application in light-induced controlled free radical polymerization
In controlled radical polymerization technology, condensation of aldehyde monomers and amino monomers is used to prepare conjugated microporous polymers as catalysts, and the photo-induced catalysis without metal and enzymes is achieved, and the photo-induced in the prior art is solved The problem of insufficient catalytic efficiency and environmental protection under conditions has achieved efficient, economical and environmentally friendly polymerization reaction effects.
Patent Information
- Application Number
- CN202310305431.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-03-27
AI Technical Summary
The existing controlled radical polymerization technology is difficult to achieve efficient catalysis without metal and enzyme under light-induced conditions, and the traditional methods lack durability and environmental protection for multiple uses.
Condensation reaction of aldehyde monomer and amino monomer under specific solvent and catalyst conditions is used to prepare conjugated microporous polymers as catalysts for reversible complexation-mediated polymerization reactions to achieve a metal-free and enzyme-free heterocatalytic system. Controllable radical polymerization is carried out under visible light.
A metal-free and enzyme-free catalytic system has been built with high economic benefits and good safety. It can maintain good catalytic activity in multiple cycles and does not require water or other solvents, making it more environmentally friendly and green.
Smart Images

Figure CN116217854B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material preparation, and specifically relates to a conjugated microporous polymer and a preparation method thereof, and application of the conjugated microporous polymer in visible light-induced controllable free radical polymerization reaction. Background Art
[0002] In recent years, controlled radical polymerization (CRP) has been widely developed and applied to prepare polymer materials with precise structure, controllable molecular weight and uniform distribution. Methods of controlled radical polymerization are also being continuously developed, such as nitroxide-stabilized radical polymerization (NMP), atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer radical polymerization (RAFT), reversible chain transfer catalytic polymerization (RTCP), reversible complexation mediated polymerization (RCMP), etc. These polymerization techniques have opened up a new path for the diversity of polymer structures and functions. Compared with the traditional thermally initiated polymerization process, the conditions of photoinduced radical polymerization are milder, which provides an important way to achieve a wider application of polymers.
[0003] Compared with other controlled living free radical polymerizations, the advantage of reversible complexation-mediated polymerization is not only the variety of catalyst forms, but also its suitability for the controlled polymerization of various functional monomers. RCMP can be used to synthesize polymers with clear composition, controllable molecular weight, and relatively uniform molecular weight. These polymers are widely used in clinical medicine, biomedicine, health care, cosmetics, and pesticide release.
[0004] Conjugated microporous polymers (CMPs) are a very promising class of organic porous materials with the advantages of π-conjugation, large specific surface area, high stability, precise control of micropore size and volume, high chemical stability and thermal stability, etc. They can be reused many times, have high catalytic efficiency, strong applicability, and are suitable for large-scale applications. They have achieved important applications in many fields such as gas adsorption, chemical sensing, heterogeneous catalysis, energy storage and conversion, etc. Since the π-conjugation of conjugated microporous polymer materials will affect the conduction of electrons and holes, CMPs have potential application prospects in the light-induced RCMP process. Summary of the invention
[0005] In order to broaden the application of conjugated microporous polymer (CMPs) materials in the field of light-induced RCMP polymerization, the present invention provides a CMPs material and uses the CMPs material for catalytic polymerization of RCMP.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A conjugated microporous polymer material, the unit structure of which is:
[0008] .
[0009] The conjugated microporous polymer material is prepared by condensing aldehyde monomers and amino monomers in the presence of a solvent and a catalyst.
[0010] The molar ratio of the aldehyde monomer to the amino monomer is 3:2.
[0011] Furthermore, the aldehyde monomer is one or more of 4'4-biphenyl dicarboxaldehyde, terephthalaldehyde, 2,5-dichloroterephthalaldehyde, and 1,4-di(4-aldehyde phenyl)benzene.
[0012] Furthermore, the amino monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine.
[0013] Furthermore, the solvent is one or more of 1,2-dichlorobenzene, ethanol, n-butanol, 1,4-dioxane, toluene, petroleum ether, N,N-dimethylformamide, and tetrahydrofuran.
[0014] Furthermore, the catalyst is a 3-6 mol / L acetic acid solution.
[0015] Furthermore, the condensation reaction temperature is 80-180°C and the time is 72-120h.
[0016] The conjugated microporous polymer material is used as a catalyst to catalyze a reversible complexation-mediated polymerization reaction, and a polymer with a certain molecular weight and low dispersion (PDI=1.04-1.25) can be obtained, and has the advantages of being reusable, having high catalytic efficiency, and having strong applicability. The specific application method is to mix the conjugated microporous polymer material as a photocatalyst with a monomer and an initiator under a nitrogen or argon atmosphere, and to carry out a reversible complexation-mediated polymerization reaction under visible light irradiation.
[0017] Furthermore, the monomer is one or more of methyl methacrylate (MMA), benzyl methacrylate (BzMA), methoxyethyl methacrylate (MEMA), glycidyl methacrylate (GMA), 2-diethylaminoethyl methacrylate (HEA), N,N-dimethylacrylamide (DMA), dimethylaminoethyl methacrylate (DEAEMA), and polyethylene glycol methyl ether acrylate (PEGMA).
[0018] Furthermore, the initiator is any one of 2-iodo-2-methylpropionitrile, ethyl 2-iodophenylacetonitrile, 2-iodophenylacetonitrile, and ethyl 2-iodo-2-methylpropionate.
[0019] The beneficial effects and outstanding advantages of the present invention are:
[0020] 1. By using the conjugated microporous polymer material obtained by the present invention to carry out a controllable free radical polymerization reaction induced by the full spectrum of visible light, a metal-free and enzyme-free heterogeneous catalytic system can be constructed, which takes into account both economic benefits and safety.
[0021] 2. The obtained conjugated microporous polymer material is used in a visible light-induced controlled free radical polymerization reaction without the need for water or other solvents, which is more environmentally friendly and green.
[0022] 3. The conjugated microporous polymer material obtained by the present invention can still maintain good catalytic activity in multiple cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the XRD pattern of TAPT-S3-CMP obtained in Example 3.
[0024] Figure 2 This is the SEM image of TAPT-S3-CMP obtained in Example 3.
[0025] Figure 3 The infrared characterization image (a) and carbon spectrum (b) of TAPT-S3-CMP obtained in Example 3.
[0026] Figure 4 This is a comparison of infrared spectra of the products obtained when TAPT-S2-CMP obtained in Example 4 was placed in MMA monomer for 0 h and 24 h.
[0027] Figure 5 The monomer conversion rate and dispersion degree of the polymer obtained after three reactions as described in Example 9 are shown.
[0028] Figure 6 A graph showing the results of an on-off light experiment conducted for Application Example 10. DETAILED DESCRIPTION
[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0030] Example 1 Synthesis of catalyst TAPT-S3-CMP:
[0031] 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 18 mg) and 4'4-biphenyldicarboxaldehyde (S3, 18.33 mg) were introduced into a Schlenk tube, and then 1,2-dichlorobenzene (1.9 mL), n-butanol (0.1 mL) and acetic acid solution (0.1 mL, 4 M) were added. After ultrasonication for 3 minutes, the mixture was quickly frozen with liquid nitrogen, and after freeze-pump-thaw three times, the mixture was heated at 130°C for 3 days to produce a yellow precipitate, which was then washed with tetrahydrofuran, extracted with tetrahydrofuran for 1 day, and dried in vacuo to obtain the final product with a yield of 65%.
[0032] Example 2 Synthesis of catalyst TAPT-S3-CMP:
[0033] 2,4,6-Tris(4-aminophenyl)-1,3,5-triazine (TAPT, 18 mg) and 4'4-biphenyldicarboxaldehyde (S3, 16 mg) were introduced into a Schlenk tube, and then 1,2-dichlorobenzene (1.9 mL), n-butanol (0.1 mL) and acetic acid solution (0.1 mL, 4 M) were added. After ultrasonication for 3 minutes, it was quickly frozen with liquid nitrogen, and after freeze-pump-thaw 3 times, it was heated at 150°C for 3 days to produce a yellow precipitate, which was then washed with tetrahydrofuran, and washed with tetrahydrofuran Soxhlet extraction for 1 day. The final product was obtained by vacuum drying with a yield of 67%.
[0034] Example 3 Synthesis of catalyst TAPT-S3-CMP:
[0035] 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 15 mg) and 4'4-biphenyldicarboxaldehyde (S3, 13.5 mg) were introduced into a Schlenk tube, and then 1,2-dichlorobenzene (0.5 mL), n-butanol (0.5 mL) and acetic acid solution (0.1 mL, 5 M) were added. After ultrasonication for 3 minutes, the mixture was quickly frozen with liquid nitrogen, and after freeze-pump-thaw three times, the mixture was heated at 120°C for 3 days to produce a yellow precipitate, which was then washed with tetrahydrofuran, extracted with tetrahydrofuran for 1 day, and dried in vacuo to obtain the final product with a yield of 77%.
[0036] Example 4 Synthesis of catalyst TAPT-S2-CMP:
[0037] 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 15 mg) and terephthalaldehyde (S2, 11.8 mg) were introduced into a Schlenk tube, and then 1,2-dichlorobenzene (1 mL), 1,4-dioxane (0.5 mL) and acetic acid solution (0.1 mL, 4 M) were added. After ultrasonication for 3 minutes, the mixture was quickly frozen with liquid nitrogen, and after freeze-pump-thaw three times, it was heated at 120°C for 3 days to produce a yellow-green precipitate, which was then washed with tetrahydrofuran, extracted with tetrahydrofuran for 1 day, and dried in vacuo to obtain the final product with a yield of 77%.
[0038] Example 5 Synthesis of catalyst TAPT-S2-CMP:
[0039] 2,4,6-Tris(4-aminophenyl)-1,3,5-triazine (TAPT, 15 mg) and terephthalaldehyde (S2, 13.5 mg) were introduced into a Schlenk tube, and then mesitylene (1.5 mL), 1,4-dioxane (0.5 mL) and acetic acid solution (0.1 mL, 3 M) were added. After ultrasonication for 3 minutes, the mixture was quickly frozen with liquid nitrogen and freeze-pump-thawed 3 times. The mixture was heated at 120°C for 3 days to produce a yellow-green precipitate, which was then washed with tetrahydrofuran, extracted with tetrahydrofuran for 1 day, and dried in vacuo to obtain the final product with a yield of 71%.
[0040] Example 6 Synthesis of catalyst TAPT-S2-CMP:
[0041] 2,4,6-tris(4-aminophenyl)-1,3,5-triazine (TAPT, 15 mg) and terephthalaldehyde (S2, 15.5 mg) were introduced into a Schlenk tube, and then mesitylene (1.4 mL), n-butanol (0.3 mL) and acetic acid solution (0.1 mL, 6 M) were added. After ultrasonication for 3 minutes, the mixture was quickly frozen with liquid nitrogen and freeze-pump-thawed 3 times. The mixture was heated at 120°C for 3 days to produce a yellow-green precipitate, which was then washed with tetrahydrofuran, extracted with tetrahydrofuran and washed for 1 day, and dried in vacuo to obtain the final product with a yield of 65%.
[0042] Figure 1 The XRD diagram of the obtained product is shown in Figure 2. As can be seen from the figure, there is no diffraction characteristic peak, indicating that the material is an amorphous structure, which is consistent with the structural characteristics of CMPs materials.
[0043] Figure 2 The SEM image of the obtained product is shown in Figure 1. The irregular morphology shown in the image also proves that the obtained product is an amorphous structural material.
[0044] Figure 3 The infrared characterization image (a) and carbon spectrum (b) of the obtained product are shown. Figure 3It can be seen that with the disappearance of the -NH2 bond in the raw material TAPT and the -CHO bond in the raw material S3, the product TAPT-S3-CMP showed obvious -C=N- bonds, which indicated the successful synthesis of TAPT-S3-CMP (a). At the same time, the appearance of the -C=N- characteristic peak at 151ppm in the solid NMR carbon spectrum and the characteristic peak of C in the -C=N- bond at 158.5ppm further confirmed the successful synthesis of TAPT-S3-CMP (b).
[0045] Figure 4 This is a comparison of the infrared spectra of the products obtained by placing TAPT-S2-CMP obtained in Example 4 in MMA monomer for 0h and 24h. As can be seen from the figure, there is no obvious change in the characteristic peaks before and after the catalyst is soaked, indicating that TAPT-S2-CMP can maintain good stability in the catalytic polymerization of MMA monomer.
[0046] Application Example 1
[0047] MMA (2 mL), 2-iodophenylacetonitrile (12 μL), and TAPT-S3-CMP (10 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The resulting mixture was illuminated by a white light LED (13 W m -1 , 15 mW·cm -2 ) and samples were collected at regular intervals at room temperature. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 5400 g mol -1 , Mw / Mn=1.21.
[0048] Application Example 2
[0049] MEMA (2 mL), 2-iodo-2-methylpropionitrile (21 μL), and TAPT-S3-CMP (10 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The resulting mixture was illuminated by a white light LED (13 W m -1 , 15mW·cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 6600 g mol -1 , Mw / Mn=1.13.
[0050] Application Example 3
[0051] BZMA (2 mL), ethyl 2-iodophenylacetate (26 μL), and TAPT-S2-CMP (10 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The resulting mixture was illuminated by a white light LED (13 W m -1 ,15mW·cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 5900 g mol -1 , Mw / Mn=1.19.
[0052] Application Example 4
[0053] BZMA (2 mL), ethyl 2-iodophenylacetate (26 μL), and TAPT-S3-CMP (5 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The mixture was then illuminated by a white light LED (13 W m -1 , 15mW·cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 4900 g mol -1 , Mw / Mn=1.08.
[0054] Application Example 5
[0055] DEAEMA (2 mL), ethyl 2-iodo-2-methylpropionate (19 μL), and TAPT-S3-CMP (5 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The mixture was then illuminated by a white light LED (13 W m -1 , 15mW cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 6500 g mol -1 , Mw / Mn=1.06.
[0056] Application Example 6
[0057] GMA (2 mL), 2-iodo-2-methylpropionitrile (27 μL), and TAPT-S2-CMP (5 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The mixture was then illuminated by a white light LED (13 W m-1 , 15 mW·cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 5500 g mol -1 , Mw / Mn=1.15.
[0058] Application Example 7
[0059] MEMA (2 mL), 2-iodophenylacetonitrile (30 μL), and TAPT-S3-CMP (5 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The mixture was then illuminated by a white light LED (13 W m -1 , 15 mW·cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 6100 g mol -1 , Mw / Mn=1.18.
[0060] Application Example 8
[0061] DEAEMA (2 mL), 2-iodo-2-methylpropionitrile (25 μL), and TAPT-S2-CMP (10 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The mixture was then illuminated by a white light LED (13 W m -1 , 15mW·cm -2 ) and samples were collected at room temperature at regular intervals. GPC analysis was used to characterize the molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The results showed that the molecular weight Mn of the polymer obtained after 10 h of reaction was 6400 g mol -1 , Mw / Mn=1.16.
[0062] Application Example 9
[0063] MMA (2 mL), 2-iodo-2-methylpropionitrile (15 μL), and TAPT-S3-CMP (10 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The mixture was then illuminated by a white light LED (13 W m -1 , 15 mW·cm -2After irradiation for 10 hours under 40 °C, a small amount of sample was collected and analyzed by GPC to characterize its molecular weight (Mn) and molecular weight dispersity (Mw / Mn). The used catalyst was reprecipitated with methanol solution three times, centrifuged, and vacuum dried, and then used as a catalyst again in the above polymerization reaction. This cycle was repeated twice.
[0064] Figure 5 The conversion rate and corresponding dispersity of the polymer obtained after three experiments. It can be seen from the figure that the catalytic performance of the catalyst did not decrease significantly after two cycles, indicating that the catalyst has good recyclability and reusability.
[0065] Application Example 10
[0066] MMA (2 mL), 2-iodo-2-methylpropionitrile (12 μL), and TAPT-S3-CMP (10 mg) were added to a 3 ml glass bottle. The glass bottle was tightly plugged with a rubber stopper and degassed under nitrogen for 30 min. The resulting mixture was illuminated by a white light LED (13 W m -1 , 15 mWcm -2 ) for two hours, then stop irradiation and place the glass bottle in a dark place. Take a small amount of polymer with a syringe and characterize it by GPC (determine the molecular weight and calculate ln[M0] / [M t ] value), when the glass bottle was placed in the dark for 30 minutes, another sample was taken for characterization by GPC. -1 , 15 mW cm -2 ) for two hours, and repeat the above steps until the data measurement after 2 hours of red light irradiation is completed.
[0067] Figure 6 This is the result of the switching light experiment of TAPT-S3-CMP obtained in Example 3. Figure 6 It can be seen that the catalyst has the ability to induce RCMP across the entire spectrum, and the molecular weight basically does not increase after being placed in the dark for 0.5 hours, indicating that the polymerization reaction induced by the catalyst can be controlled by switching the light on and off.
[0068] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. Application of a conjugated microporous polymer material in catalyzing a reversible complexation-mediated polymerization reaction, characterized in that: The unit structure formula of the conjugated microporous polymer material is: ; The preparation method is to prepare the conjugated microporous polymer material by condensing aldehyde monomer and amino monomer in the presence of solvent and catalyst; The aldehyde monomer is 2,5-dichloroterephthalaldehyde; the amino monomer is 2,4,6-tris(4-aminophenyl)-1,3,5-triazine; the catalyst is 3-6 mol / L acetic acid solution; When used, the conjugated microporous polymer material is used as a photocatalyst to carry out a reversible complexation-mediated polymerization reaction with a monomer and an initiator under a nitrogen or argon atmosphere and the action of visible light; The monomer is one or more of methyl methacrylate, benzyl methacrylate, methoxyethyl methacrylate, glycidyl methacrylate, 2-diethylaminoethyl methacrylate, N,N-dimethylacrylamide, dimethylaminoethyl methacrylate, and polyethylene glycol methyl ether acrylate; the initiator is any one of 2-iodo-2-methylpropionitrile, ethyl 2-iodophenylacetonitrile, 2-iodophenylacetonitrile, and ethyl 2-iodo-2-methylpropionate.
2. The use according to claim 1, characterized in that: The molar ratio of the aldehyde monomer to the amino monomer is 3:
2.
3. The use according to claim 1, characterized in that: The solvent is one or more of 1,2-dichlorobenzene, ethanol, n-butanol, 1,4-dioxane, toluene, petroleum ether, N,N-dimethylformamide, and tetrahydrofuran.
4. The use according to claim 1, characterized in that: The condensation reaction temperature is 80-180° C. and the reaction time is 72-120 hours.
Citation Information
Patent Citations
Conjugated microporous polymer, preparation method thereof and application of conjugated microporous polymer in visible-light-induced controllable free radical polymerization
CN112724345A
Imino covalent organic framework polymer and preparation method and application thereof, ammonia gas sensor and preparation method thereof, and ammonia gas sensing detection method
CN113045722A